Peran strategi komunikasi public relation dalam membangun citra positif perusahaan - Ramadhani, Nayla Salsabila (Maliki Interdisciplinary Journal, 2025)
A positive image of an organization or company in the public eye. In the digital era of rapid information flow, PR’s function is not only limited to disseminating information, but also managing reputation and long-term relationships with the public. The research method used was descriptive qualitative, reviewing various literature, case studies, and theories of organizational communication and image management. The results show that an effective PR communication strategy must be oriented towards transparency, message consistency, and public engagement through various media, both conventional and digital. By implementing the right communication strategy, organizations can build, maintain, and even improve a positive image in the public eye.